Cashew Gum (Anacardium occidentale) as a Potential Source for the Production of Tocopherol-Loaded Nanoparticles: Formulation, Release Profile and Cytotoxicity - Loureiro, Kahynna C. (2021)
Every year, more than thirty thousand tons of Cashew gum (Anacardium occidentale, family: Anacardiaceae) are produced in Brazil; however, only a small amount is used for different applications in foodstuff and in pharmaceutical industries. As a raw material for the production of drug delivery systems, cashew gum is still regarded as an innovative compound worth to be exploited. In this work, cashew gum was extracted from the crude exudate of cashew tree employing four methodologies resulting in a light brown powder in different yields (40.61% to 58.40%). The total ashes (0.34% to 1.05%) and moisture (12.90% to 14.81%) were also dependent on the purification approach. FTIR spectra showed the typical bands of purified cashew gum samples, confirming their suitability for the development of a pharmaceutical product. Cashew gum nanoparticles were produced by nanoprecipitation resulting in particles of low polydispersity (<0.2) and an average size depending on the percentage of the oil. The zeta potential of nanoparticles was found to be below 20 mV, which promotes electrostatic stability. Encapsulation efficiencies were above 99.9%, while loading capacity increased with the increase of the percentage of the oil content of particles. The release of the oil from the nanoparticles followed the Korsmeyer–Peppas kinetics model, while particles did not show any signs of toxicity when tested in three distinct cell lines (LLC-MK2, HepG2, and THP-1). Our study highlights the potential added value of using a protein-, lignans-, and nucleic acids-enriched resin obtained from crude extract as a new raw material for the production of drug delivery systems.